THE INFLUENCE OF INNOVATION, COMPETITIVE ADVANTAGE AND LOCATION ON THE DECISION TO BUY KOPI KENANGAN IN JAKARTA WITH LIFE STYLE AS A MODERATOR - Imam Suryono; Alya Kamelia Puspita; Diansyah (RADJA PUBLIKA, 2026)
This study examines the effects of innovation, competitive advantage, and location on consumers’ purchasing decisions for Kopi Kenangan in Jakarta, with lifestyle serving as a moderating variable. A quantitative approach was applied using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. Data were collected through structured questionnaires from 150 consumers who had purchased Kopi Kenangan products in Jakarta. The results indicate that competitive advantage, location, and lifestyle have positive and significant effects on purchasing decisions, whereas innovation has no significant influence, suggesting that consumers do not consider product innovation a key determinant when purchasing Kopi Kenangan. In addition, lifestyle significantly strengthens the relationship between competitive advantage and purchasing decisions but does not moderate the effect of innovation. Lifestyle also negatively moderates the relationship between location and purchasing decisions, indicating that consumers with modern lifestyles place greater emphasis on digital convenience, product quality, and brand reputation than on physical store accessibility. These findings provide valuable managerial and academic implications.